2019
DOI: 10.3233/jifs-179023
|View full text |Cite
|
Sign up to set email alerts
|

Online Hate Speech against Women: Automatic Identification of Misogyny and Sexism on Twitter

Abstract: Patriarchal behavior, such as other social habits, has been transferred online, appearing as misogynistic and sexist comments, posts or tweets. This online hate speech against women has serious consequences in real life, and recently, various legal cases have arisen against social platforms that scarcely block the spread of hate messages towards individuals. In this difficult context, this paper presents an approach that is able to detect the two sides of patriarchal behavior, misogyny and sexism, analyzing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(55 citation statements)
references
References 17 publications
(29 reference statements)
1
44
0
10
Order By: Relevance
“…Concluding, evaluating all the indexes together, we notice that our dictionarybased algorithm performs very well. In particular, it outperforms the supervised feature-based models of Frenda et al (2019) and of Foucalt et al 2016which report an AC of 76% and a F1 score equal to 72%, respectively. At the same time our method performs more similarly (despite anyway outperforming such methods of more than 8 percentage points) to the computationally intensive deep learning methods implemented in Stowe et al (2019) and Nizzoli et al (2019), which obtain values of the F1 score equal to 83% and 90%, respectively.…”
Section: Table 3 Here (Now At the End Of The File)mentioning
confidence: 81%
See 1 more Smart Citation
“…Concluding, evaluating all the indexes together, we notice that our dictionarybased algorithm performs very well. In particular, it outperforms the supervised feature-based models of Frenda et al (2019) and of Foucalt et al 2016which report an AC of 76% and a F1 score equal to 72%, respectively. At the same time our method performs more similarly (despite anyway outperforming such methods of more than 8 percentage points) to the computationally intensive deep learning methods implemented in Stowe et al (2019) and Nizzoli et al (2019), which obtain values of the F1 score equal to 83% and 90%, respectively.…”
Section: Table 3 Here (Now At the End Of The File)mentioning
confidence: 81%
“…This estimated classifier is then adopted for predicting the category of a new tweet. This approach is used for example by Frenda et al (2019), who adopt a common method in machine learning as Support Vector Machine (SVM) to automatically detect sexist and misogyny on Twitter. In particular, this study uses, as training dataset, the freely available corpora known as "Automatic Misogyny Identification -IBEREVAL 2018" 5 and considers, as input variables, some lexical and stylistic features of the post.…”
Section: Related Workmentioning
confidence: 99%
“…The battle against equality for men and women in cyberspace has intensified online hate speech (Frenda et al, 2019) The amount of hateful material reported in social media against women is even worse than that of their friends. This material offers a model of sexual animosity and prejudices from which AI can benefit.…”
Section: The Consequences Of Gender-biased Artificial Intelligencementioning
confidence: 99%
“…Frenda et al (2019) and ofFoucalt et al (2016) which report an AC of 76% and a F 1 score equal to 72%, respectively. At the same time our method performs more similarly (despite anyway outperforming such methods of more than 8 percentage points) to the computationally intensive deep learning methods implemented inStowe et al (2019) andNizzoli et al (2019), which obtain values of the F 1 score equal to 83% and 90%, respectively.…”
mentioning
confidence: 92%